Mass-media in Venezuela: Ownership, Legislation and the Role of Private Broadcasters - González-Ramírez, José Fabián (2015)
Latin America is a region where the modelof mass media as a public service hasbeen historically neglected by commercialmarketing and consumption ratings.Therefore, it is worthy to think about thesocial role media owners play there. Thisarticle analyzes the Venezuelan case because theemergence of the Bolivarian Revolution in thatcountry in the first decade of the 21st. century,is considered by the capitalists broadcasters, as aprocess that threatens the continuity of patrimonialrights of private TV. channels.